Exosomes, their sources, and possible uses in cancer therapy in the era of personalized medicine - Tomas Zemanek; Lubos Danisovic; Andreas Nicodemou (Journal of Cancer Research and Clinical Oncology)
Abstract Despite significant advances in immunotherapy, its efficacy in solid tumors remains limited. Exosomes, a primary type of extracellular vesicles, can transport diverse intracellular molecules to nearby or distant cells and organs, facilitating numerous biological functions. Research has shown that exosomes have the dual ability to both activate and suppress the immune system. Their potential as anticancer vaccines arise from the capacity to carry antigens and major histocompatibility complex (MHC) molecules. Exosomes derived from blood, saliva, urine, and cerebrospinal fluid serve as promising biomarkers for cancer diagnosis and prognosis. Recent advancements in exosome-based therapy have highlighted its utility in drug delivery and immunotherapy. This review examines the composition and sources of exosomes within the immune microenvironment of solid tumors and delves into the mechanisms and pathways through which exosomes impact immunotherapy. We further explore the clinical potential of engineered exosomes and exosome vaccines in solid tumor immunotherapy. These insights may pave the way for exosome-based strategies in cancer diagnosis, treatment, and prognosis, enhancing the effectiveness of immunotherapy for solid tumors.